THE UNCITRAL MODEL LAW ON INTERNATIONAL CREDIT TRANSFERS: ENHANCING EFFICIENCY, LEGAL UNIFORMITY, AND ERROR MANAGEMENT IN GLOBAL FINANCIAL TRANSACTIONS - Aminjon Qalandarov (Journals Park Publishing, 2024)
The UNCITRAL Model Law on International Credit Transfers, adopted in 1992, serves as a pivotal legal framework designed to harmonize and improve the efficiency of cross-border credit transfers. This article explores the Model Law's comprehensive approach to defining the rights and obligations of all parties involved in international credit transfers, including the originator, the originator's bank, intermediary banks, and the beneficiary's bank. It delves into the detailed provisions governing the execution process, liability for errors, and mechanisms for cancellation and refund of transfers. Furthermore, the article discusses the Model Law's significant role in promoting legal uniformity across different jurisdictions, thereby facilitating smoother international transactions and reducing legal uncertainties. By examining these key aspects, the article underscores the importance of the UNCITRAL Model Law in ensuring the reliability, predictability, and security of global financial systems.
Keywords: UNCITRAL Model Law, International Credit Transfers, Cross-border Transactions, Legal Uniformity, Liability, Error Handling, Cancellation, Refund Mechanisms, International Banking Law, Financial Regulation.